EEG Responses to Shamanic Drumming. Does the Suggestion of Trance State Moderate the Strength of Frequency Components? - Mateusz, Konopacki; Guy, Madison (Journal of Sleep And Sleep Disorder Research, 2018)
One of the techniques used to induce trance state in shamanic ceremonies is monotonous drumming. According to previous EEG research, certain patterns of drumming cause an increase in power of alpha and theta frequencies of the listener. Present study aimed to determine, if suggestion to experience trance state could increase the relative alpha and theta amplitude and the intensity of experienced state. A group of twenty-four subjects participated in the study. Suggestion to experience trance state decreased alpha frequency power during the drumming condition. No other significant effects of suggestion or drumming were found.
Keywords: EEG; trance state; shamanic drumming; music therapy